A survey on the appropriateness of drug therapy in patients with renal dysfunction at the Internal Medicine Ward FMUI/Dr. Cipto Mangunkusumo Hospital (Faculty of Medicine Universitas Indonesia, 2009)
Aim Dose adjusment and drug selection is important in patient with renal dysfuction.This study was aimed to assess the accuracy of dose adjustment and drug selection for renal dysfunction patient at the Internal Medicine Ward FMUI/Dr. Cipto Mangunkusumo Hospital, Jakarta. Methods Patients ≥ 18 years old with estimated creatinine clearance < 60 mL/minute based on Cockroft-Gault formula were included in this study. The drugs assessed were those excreted by the kidney or having nephrotoxic effect. The appropriateness of drug selection is assessed based on the preserce or not contraindication or potential of drug-drug interaction. The accuracy of dose adjustment were assessed based on information available in various textbooks, literatures, and drug brochures. Data were collected between May to July 2007. Results Data obtained from 43 patients met the inclusion criterias demonstrated that 164 out of 385 drug prescriptions were mainly eliminated by the kidney or have nephrotoxic characteristic. Out of 164 drug prescriptions, 142 (86.5%) were appropriately adjusted, while the other 22 (13.5%) were inappropriately adjusted for the dose. There was only one contraindication for the usage of the drug and 15.1% potentially drug interaction. Conclusion Dose adjustment and drug selections in patients with renal dysfunction at the Internal Medicine Ward FMUI/Dr. Cipto Mangunkusumo Hospital are conducted appropriately. (Med J Indones 2009; 18: 108-13) Key words: renal dysfunction, drug interaction, contraindication, dose adjusment